2023
DOI: 10.3847/1538-4357/acd9ce
|View full text |Cite
|
Sign up to set email alerts
|

QUOTAS: A New Research Platform for the Data-driven Discovery of Black Holes

Abstract: We present QUOTAS, a novel research platform for the data-driven investigation of supermassive black hole (SMBH) populations. While SMBH data—observations and simulations—have grown in complexity and abundance, our computational environments and tools have not matured commensurately to exhaust opportunities for discovery. To explore the BH, host galaxy, and parent dark matter halo connection—in this pilot version—we assemble and colocate the high-redshift, z > 3 quasar population alongside simulated data at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 183 publications
0
1
0
Order By: Relevance
“…The QUOTAS data (Natarajan et al 2023) that support the findings of this study are publicly available at the Google Kaggle platform and can be found at https://www.kaggle. com/data sets/quotasplatform/quotas.…”
Section: Data Availabilitymentioning
confidence: 62%
“…The QUOTAS data (Natarajan et al 2023) that support the findings of this study are publicly available at the Google Kaggle platform and can be found at https://www.kaggle. com/data sets/quotasplatform/quotas.…”
Section: Data Availabilitymentioning
confidence: 62%